2015
DOI: 10.1155/2015/694853
|View full text |Cite
|
Sign up to set email alerts
|

Turkish Version of the Cognitive Distortions Questionnaire: Psychometric Properties

Abstract: Cognitive distortions are interrelated with all layers of cognitions, and they may be part of the treatment once they are accessed, identified, labeled, and changed. From both a research and a clinical perspective, it is of utmost importance to disentangle cognitive distortions from similar constructs. Recently, the Cognitive Distortions Questionnaire (CD-Quest), a brief and comprehensive measure, was developed to assess both the frequency and the intensity of cognitive distortions. The aim of the present stud… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
13
1
2

Year Published

2017
2017
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 14 publications
(19 citation statements)
references
References 41 publications
3
13
1
2
Order By: Relevance
“…Thus, we used the combined total score as broader marker of cognitive distortion severity. As predicted, and consistent with all previous studies on the measure (Batmaz et al, 2015; de Oliveira et al, 2015; Kostoglou & Pidgeon, 2016; Morrison et al, 2015), confirmatory factor analysis and post hoc exploratory factor analysis demonstrated that the CD-Quest possessed a unidimensional factor structure. Our results confirm this structure in an adult sample of English-speaking SAD patients, providing further evidence that one broad factor underlies the tendency to experience the types of thinking patterns identified in the CD-Quest.…”
Section: Discussionsupporting
confidence: 89%
See 4 more Smart Citations
“…Thus, we used the combined total score as broader marker of cognitive distortion severity. As predicted, and consistent with all previous studies on the measure (Batmaz et al, 2015; de Oliveira et al, 2015; Kostoglou & Pidgeon, 2016; Morrison et al, 2015), confirmatory factor analysis and post hoc exploratory factor analysis demonstrated that the CD-Quest possessed a unidimensional factor structure. Our results confirm this structure in an adult sample of English-speaking SAD patients, providing further evidence that one broad factor underlies the tendency to experience the types of thinking patterns identified in the CD-Quest.…”
Section: Discussionsupporting
confidence: 89%
“…This finding was surprising in light of previous reports of significant correlations of the CD-Quest with the BDI-II (Batmaz et al, 2015; Morrison et al, 2015). However, the distribution of BDI-II scores was considerably positively skewed, suggesting that depression scores were uniformly low in this sample and potentially accounted for the lack of correlation.…”
Section: Discussioncontrasting
confidence: 82%
See 3 more Smart Citations